Role of Intermittent Self Catheterization after Cauda Equina Syndrome Surgery. - Muhammad Mujahid Sharif; Syed Atif Mehmood Kazmi; Masood Mukhtar; Adil Aziz Khan (Journal of Rawalpindi Medical College, 2018)
Background: To determine the effectiveness and safety of intermittent self catheterization in cauda equina patients who have lost the bladder control. Methods : In this prospective study patients with symptoms and signs of cauda equina syndrome, due to lumbar disc herniation confirmed by relevant MRI ,were included. Emergency surgery was performed and post operatively these patients were taught the technique of intermittent self catheterization. After full aseptic measures patients were asked to sit on the chair and identify the meatus. Catheter was slowly inserted into the bladder,uptil the urine output was obtained. Pressure on the lower abdomen was applied to help in emptying the bladder. Nelton catheter was removed and was kept in a bottle of clean water. After couple of attempts patients learnt to pass the catheter. Patient was asked and helped to do this activity 3 to 4 times a day. The patient was discharged from the hospital only when he/she was confident enough to catheterize himself/herself. Initially patients were kept on biweekly follow up and later on monthly basis. Results : Majority (86%) continued to undergo intermittent self catheterization, but 14% , elderly patients, experienced insertion difficulty and discontinued intermittent self catheterization. Ten patients (24%) had bacteriuria during the procedure. Epididymitis was seen in 2%. There were no urethral complications suggesting that the self-lubricating Nelton catheters are safe and less traumatic. Conclusion: Intermittent self catheterization is a safe, effective treatment and is associated with improved quality of life in cauda equina syndrome patients.